Heparin and non-anticoagulant heparin attenuate histone-induced inflammatory responses in whole blood - Hogwood, John (PLoS One, 2020)
Cytotoxic and pro-inflammatory histones are present in neutrophil extracellular traps (NETs) and are elevated in blood in several inflammatory conditions, sepsis being a major example. Compounds which can attenuate activities of histones are therefore of interest, with heparin being one such material that has previously been shown to bind to histones. Heparin, a successful anticoagulant for nearly a century, has been shown experimentally to bind to histones and exhibit a protective effect in inflammatory conditions. In the present study carried out in whole blood, heparin and selectively desulfated heparin reduced histone induced inflammatory markers such as interleukin 6 (IL 6), interleukin 8 (IL 8) and tissue factor and C3a, a complement component. The selectively desulfated heparins, with reduced anticoagulant activities, retained a high degree of effectiveness as an anti-histone agent, whereas fully desulfated heparin was found to be ineffective. The results from this study indicate that the presence of sulfate and other specific structural features are required for heparin to attenuate the inflammatory action of histones in whole blood.